Discovery of the Genomic Region and Candidate Genes of the Scarlet Red Flesh Color (Yscr) Locus in Watermelon (Citrullus Lanatus L.) - Li, Na; Shang, Jianli; Wang, Jiming; Zhou, Dan; Li, Nannan; Ma, Shuangwu (Frontiers in Plant Science, 2020)
The flesh color of watermelon (Citrullus lanatus) is an important fruit quality trait that helps to determine fruit attractiveness and is potentially beneficial to human health. Previous inheritance analyses determined that a single dominant gene, Yscr, produces the scarlet red flesh color rather than the coral red flesh color in watermelon. However, no genomic region or gene-based molecular markers for the locus Yscr have been reported thus far. In the present study, two high-density genetic maps and whole-genome variation detection aided by genome resequencing were first map the flesh color locus Yscr to a small region on chromosome 6 based on two independent populations derived from two scarlet red-fleshed lines and two coral red-fleshed lines. Two major quantitative trait loci located in the same genomic regions were identified in the F2 and BC1P2 populations and explained 90.36% and 75.1% of the phenotypic variation in flesh color, respectively. Based on the genetic variation in the two parental lines, newly developed PCR-based markers narrowed the Yscr region to 34 Kb. Of the six putative genes in this region, four encoded glycine-rich cell wall structural proteins, which implied that a new regulatory mechanism might occur between scarlet red- and coral red-fleshed in watermelon. Moreover, the genotypes of two newly developed InDel markers (InDel27_fc6 and InDel27_fc6) were completely consistent with the phenotypes in the F2 and BC1P2 populations and all 56 scarlet red-fleshed watermelon accessions. The results presented here provide valuable information for marker-assisted selection of flesh color breeding and the functional validation of candidate genes in watermelon.